Identifikasi Kuliner Lokal Indonesia dalam Pembelajaran Bahasa Inggris - Agnes Siwi Purwaning Tyas (Sekolah Vokasi, Universitas Gadjah Mada, 2017)
This study is aimed at identifying the representation of local foods and beverages in English textbooks used in Indonesia. Based on the current curriculum, character building should be promoted as one of the learning goals. This effort is to maintain and strengthen students’ cultural roots and identity in this globalized world. The integration of local culture in the textbooks will help to provide exposures of both cultures and facilitate cultural dissemination of both local and global values. The result of content analysis on 36 English textbooks used in elementary schools to senior high schools in Indonesia shows how the spoken and written texts accommodate the promotion of Indonesian local cultures, particularly the local culinary. The texts mention the names of several local foods and beverages from Indonesia, such as nasi goreng, bakmi, soto, gudeg, rica-rica, klepon, and es palu butung. Based on the questionnaire results, the representation of local culinary in the textbooks can promote local identity, disseminate culture, and promote local tourism. However, the integration is still considered insufficient to disseminate the culture and promote local identity because the books have not accommodated all cultural elements in Indonesia.